Social networking and libraries - Banek Zorica, Mihaela (Array, 2012)
Observing the changes in the information landscape and new emerging online services, one type of service has really taken the online users by storm – social networking. Adopting the simple Web 2.0 principles such as harnessing the powers of the users and free signup, social networks have built a very large user base and became very interesting to different companies as a marketing tool. Today, the most popular social network globally is Facebook. With more than 500 million users worldwide, and more than half of them using Facebook on a daily basis, the marketing potential of the Facebook platform becomes obvious. As Facebook became more and more popular, different non-profit information institutions, such as libraries, began exploring ways in which they can reach potential users. The authors present the results of the research on Croatian libraries presence on Facebook, the most popular social network worldwide and in Croatia. The research was based on the analysis of the number and type of Croatian libraries present on Facebook, types of their representation (group/profile/page), number of subscribers and maintenance frequency